Fungal transformation of carbamazepine and study their metabolites through NMR and LCMS method / Nurfarahana Hafzan Mahmud - Mahmud, Nurfarahana Hafzan (2009)
Carbamazepine is an anticonvulsant and mood stabilizing agent that used primarily in treatment epilepsy and bipolar disorder, as well as trigeminal neuralgia. Microbial transformation is an effective tool for the structural modification of bioactive natural and synthetic compounds. Its application in asymmetric synthesis is increasing due to its versatility and ease. Thus, four months of study was carried out to analyze any biotransformation of Carbamazepine. In order to see the structure modification of bioactive compound using microorganisms, we investigated the metabolism of Carbamazepine (1), using Trichothecium roseum and Cunninghamella elegans. In this research, two-stage production of secondary metabolites were being employed which are primary screening and large scale production. TLC method was applied in order to do qualitative analysis of biotransformed products and HPLC was the major step that was used in identifies the presence of metabolites. On the basis of HPLC chromatogram, series of unique peaks produced, indicated biotransformation has taken place at both 6 and 12 days. Trichothecium roseum and Cunninghamella elegan biotransform Carbamazepine into various hydroxylated and oxidative metabolites.